Molecular systematic study of Southern African Oxalis (Oxalidaceae) - Oberlander, Kenneth Carl (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Botany and Zoology))—University of Stellenbosch, 2009.